Effective use of Multisensory Approach in Improving Number Concept Skills Among Pre-Schoolers: Keberkesanan penggunaan Pendekatan Multisensori dalam Meningkatkan Kemahiran Konsep Nombor Kanak-kanak Prasekolah - Lee, Mei Chiew; Abu Bakar, Kamariah (Jurnal Pendidikan Bitara UPSI, 2022)
Multisensory approach is a teaching technique that involves various senses of children such as vision, hearing, movement and touch. The involvement of all senses in teaching and learning can enhance the mastery of children's skills. This concept paper discusses the effectiveness of multisensory approaches in the development of the concept skills of the number of preschoolers. Theories relating to multisensory approach, definition of number concept, multisesory approach and importance to learning the concept of number skills of preschool children are also discussed.